Information Costs, Duration of Search, and Turnover: Theory and Applications - Wilde, Louis L. (Journal of Political Economy, 1981)
This paper uses a formal model of search over multiattribute alternatives, analyzed in a product market setting, to investigate the theoretical foundations of the empirical literature on duration of search and turnover in product markets, labor markets, and marriage markets. A number of specific emirical predictions are also derived. In particular, whether "quality" is a "search" attribute or an "experience" attribute is related to the cost of search, the cost of inspection, the price of the good, and certain properties of the market distribution of price and quality.